2010
DOI: 10.1534/genetics.110.114587
|View full text |Cite
|
Sign up to set email alerts
|

The Steroid Molting Hormone Ecdysone Regulates Sleep in Adult Drosophila melanogaster

Abstract: Ecdysone is the major steroid hormone in insects and plays essential roles in coordinating developmental transitions such as larval molting and metamorphosis through its active metabolite 20-hydroxyecdysone (20E). Although ecdysone is present throughout life in both males and females, its functions in adult physiology remain largely unknown. In this study we demonstrate that ecdysonemediated signaling in the adult is intimately involved in transitions between the physiological states of sleep and wakefulness. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
84
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(89 citation statements)
references
References 47 publications
3
84
2
Order By: Relevance
“…In addition to Notch signaling, EGF (Foltenyi et al 2007), Cyclin A (Rogulja and Young 2012), and ecdysone (Ishimoto and Kitamoto 2010) all appear to regulate sleep as well as function in their more conventional developmental roles. Overexpression of EGFR ligands in worms and flies induces sleep-like behaviors (Foltenyi et al 2007;Van Buskirk and Sternberg 2007;Raizen et al 2008), and this behavioral state change acts through EGFR in both animals.…”
Section: Conservation Of Sleep-related Functions With "Developmental"mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to Notch signaling, EGF (Foltenyi et al 2007), Cyclin A (Rogulja and Young 2012), and ecdysone (Ishimoto and Kitamoto 2010) all appear to regulate sleep as well as function in their more conventional developmental roles. Overexpression of EGFR ligands in worms and flies induces sleep-like behaviors (Foltenyi et al 2007;Van Buskirk and Sternberg 2007;Raizen et al 2008), and this behavioral state change acts through EGFR in both animals.…”
Section: Conservation Of Sleep-related Functions With "Developmental"mentioning
confidence: 99%
“…Overexpression of EGFR ligands in worms and flies induces sleep-like behaviors (Foltenyi et al 2007;Van Buskirk and Sternberg 2007;Raizen et al 2008), and this behavioral state change acts through EGFR in both animals. The initial description of nematode sleep onset as molt specific was influential in the examination of a role for ecdysone-the major Drosophila steroid hormone-in fly sleep (Ishimoto and Kitamoto 2010). Ecdysone has a critical role in developmental molting transitions, including emergence of the adult fly during eclosion, after which sleep amounts/depth are highest.…”
Section: Conservation Of Sleep-related Functions With "Developmental"mentioning
confidence: 99%
“…Immunohistochemical detection showed that EcR was widely expressed in the adult brain 44 . EcR-mediated signalling in adult flies has an important role in the formation of long-term memory) and sleep regulation 44,45 , and defective long-term memory and sleep in EcR mutants is thought to be caused by insufficient EcR-mediated signalling. Previous studies showed that deletion of EcREs in the pri-let-7-C locus caused a reduction and delay of let-7-C miRNA expression in adult flies and is associated with a let-7-C mutant phenotype 37 .…”
Section: Abnormal (N =4)mentioning
confidence: 99%
“…In particular, the average daytime wake-bout duration is drastically increased in DTS-3/+ flies, but is unaltered in EcR mutants, and administration of 20E significantly reverses the increased wake-bout duration in the DTS-3/+ flies. 2 These results imply that wake-bout durations may be controlled by an EcRindependent ecdysone signaling pathway. A molecular component that could potentially mediate such an EcR-independent ecdysone signaling pathway is a recently characterized G protein-coupled receptor, DopEcR.…”
Section: Dts-3/+ Flies (Reduced Ecdysone Levels)mentioning
confidence: 87%
“…1 In addition, we recently reported that ecdysone signaling contributes to the regulation of sleep, affecting transitions between sleep and wakefulness. 2 Here we first summarize our findings on the unconventional roles of 20E in regulating memory and sleep in adult flies. We then discuss speculative ideas concerning the stress hormone-like features of 20E, as well as the possibility that ecdysone signaling contributes to remodeling of the adult nervous system, at both the functional and structural levels, through epigenetic mechanisms.…”
mentioning
confidence: 99%